Effects of adopting Lean Management within collaborating farms : a qualitative study of Lean Lantbruk in a Swedish context - Johnsson, Carl; Weidman, Ellen (SLU/Dept. of Economics, 2016)
Higher competition and lower profitability has forced Swedish farm enterprises to adapt new market strategies. A machinery sharing collaboration between farms may increase competitiveness, reduce costs and increase shared knowledge. Since 2010 the multi-dimensional management strategy Lean Management has been adopted within Swedish farm enterprises through the project Lean Lantbruk. Lean Management implies an awareness of goal achievement and practical process tools in order to minimize costs and maximize efficiency. Further, the management strategy encourages development of relationships within the supply chain in order to fully achieve collaborative benefits. According to previous research there is need for further evaluation of the Lean Management theory in an agricultural collaboration context. The focus of this study is Lean Management in a horizontal Supply Chain Collaboration in a Swedish agricultural context with respect to machinery sharing arrangements. This study aims to increase the understanding of business culture within a collaboration between farms in Swedish agriculture where Lean Management has been implemented. A qualitative multiple case study has been conducted through in-depth interviews with three pairs of collaborating farms where Lean Management has been implemented. Interviews have also been conducted with three pairs of reference collaborations that have not implemented Lean Management. The gathered data has been analyzed through the theoretical framework which consists of theories regarding Lean Management and Supply Chain Collaboration. The results indicate a high level of perceived trust and mutuality among all collaborative parties. Hence, Lean Management does not seem to be crucial for a well functioning machinery sharing arrangement. The influence of Lean Management is perceived as low within the collaboration which may be due to a non-holistic implementation of the management strategy within the individual farm, or due to a lack of deeper relation between the collaborating parties. By recognizing the collaborating party as a part of the own business strategy a long-term partnership could be developed, which may enhance the implementation of Lean Management.